A Multi-Purpose Model for Structural Manuscript Data Storage and Representation - Riparante, Marta; Goynov, Maxim; Luchev, Detelin; Paneva-Marinova, Desislava; Pavlova, Lilia (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
This paper presents a hybrid data-model architecture developed for the Repertorium of South Slavonic Manuscripts and Copyists, a digital system for the description and analysis of Cyrillic manuscripts produced in the South Slavic lands. The model functions simultaneously as a structured storage schema, an ontological model for knowledge management, and a framework governing data representation and interface behaviour. By integrating codicological description and palaeographical analysis within a single machine-readable definition, it reduces schema–interface divergence, lowers maintenance overhead, and improves data consistency. The case study shows how domain-driven modelling can support rigorous and operationally efficient digital infrastructures for manuscript studies.